Doing More with Functions - Zaidi, Rehan (JavaScript Essentials for SAP ABAP Developers, 2017)
You learned how functions are created and how they perform a task every time you call and invoke them. You also saw different ways of using functions, parameters, and arguments. This chapter covers more advanced topics pertaining to functions. You will see how hoisting applies to functions, and learn why functions are called “first-class citizens.” You will also learn how to declare nested functions, how to apply closures to functions, and how to declare recursive functions.